THE ANALYSIS OF SEMIOTICS MODERNITY REPRESENTATION IN COMIC STRIP MICE CARTOON “INDONESIA BANGET! VOLUME 3” (The Commercium, 2022)
This paper was written based on the condition of our society that lives side by side with technology. But technology whose purpose is to help make life easier is an obstacle for them. This obstacle is based on the knowledge of our society which is still minimal about the technology itself. It was clearly photographed by Muh. Misrad in his book Mice Cartoon Indonesia Bnaget Volume 3, which is also the object of this research. The purpose of this study is to find, interpret, describe and analyze what forms of representation of society respond to modernization in the comic strip Mice Cartoon Indonesia Banget Volume 3. The research method used in compiling this scientific article is interpretive with secondary data types. The analysis technique used is qualitative using semiotic theory by Ferdinand Saussure. This theory was chosen with the aim of being able to represent in detail the signs and symbols related to technology in comics. In addition, Ferdinand De Saussure's theory was chosen because it has a more appropriate pattern to display or describe a symbol or sign in comics. Through these signs and markers, the unit of analysis will know where this research is headed. The results of this study indicate that there are representations of several pictures of the modernity of society around us which are displayed and projected through the characters in the Mice Cartoon Indonesia Banget Volume 3 comic in the “Cashless Society” series. Such as the lifestyle in the era of modernity, the inherent consumptive culture, the inherent digital divide and appearance. This result is also upheld by markers such as character dialogue, characters in the panel, setting, and expression of the characters displayed.